An evaluation of the Performance Enhancement Process (PEP) of the South African Police Service (SAPS) : a case study at Parow Police Station - Krause, Barret (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPA)--University of Stellenbosch, 2004.